Bilateral governance in outsourced services: interorganizational dynamics and consequences - Çetinkaya, Saadet. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
Rate of outsourcing, i.e., firms’ procurement of services (that can be performed in-house) from outside contractors, has been steadily increasing for the past two decades throughout the world, developed or not, and this is despite the fluctuations of the global economy. This thesis is a study on how firms that outsource services interact with the supplier firm. Specifically, it seeks to identify the antecedents, as well as the consequences, of using two alternative governance mechanisms, contract complexity and relational norms, thereby gaining insight into the dynamics of buyer-supplier interaction in outsourcing. The theoretical basis of this study is the transaction cost framework. Governance forms such as contract complexity and, especially, relational norms have been the subject of substantial interest from academics in law, economics, marketing, and organization studies in other countries in the past twenty years while being largely ignored in Turkey. This thesis volunteers to look into these ignored areas. The empirical component of the thesis includes a survey of 128 outsourcing relationships. Overall, the results provide limited support for transaction cost hypotheses.
Keywords: Contracting out.